Evaluation De La Qualit#xE9; De Gouvernance Des Institutions De Microfinancement (IMF) Et De Son Impact Sur Leur Performance: Etude De Cas De La R#xE9;gion MENA (Global Journal of Management and Business Research, 2019)
This paper raises the problem of the quality of governance of MFIs in the MENA region, and its impact on their performance. It stipulates the construction of an aggregate index, to be able to evaluate the quality of governance of institutions operating in the microfinance sector, based on the example of 7 Arab countries in the MENA region. Like the work of Wele IP. (2009), this index combines both the internal and external mechanisms of good governance within MFIs. The microfinance literature highlights strong links between the quality of governance and the performance of MFIs such as the work of: Hartarska V. (2005); Mersland R Strøm RØ. (2009); Tchakoute Tchuigoua H. (2010). This work suggests the incorporation of indices measuring the quality of governance of the MFIs of the selected sample, among the explanatory variables, through panel data, in order to determine its impact on the performance of these institutions. The study shows that these MFIs need to improve their governance system to enhance their financial and social performance.
Keywords: microfinance; gouvernance; performance